(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Some reflexions on the linguistic borders of the ancient Basque (Vasconic) especially the problems suggested by the onomastic evidence from the Tierras Altas (province of Soria) in the South of the Vasconic territory, and on the discussion of the Basque character of the western territories. Following topics are also discussed: Ancient Basque onomastics, graffiti from Iruña-Veleia, cultural and linguistic borders of Aquitanian and Vasconic, and difusion of the place names in -os.